2022
DOI: 10.1002/cam4.4546
|View full text |Cite
|
Sign up to set email alerts
|

BMI changes and the risk of lung cancer in male never‐smokers: A prospective cohort study

Abstract: Background To investigate the association between the risk of lung cancer and short‐term body mass index (BMI) changes in male never‐smokers of a large population‐based prospective study. Methods A total of 37,085 male never‐smokers from Kailuan cohort with at least ≥2 BMI measurements were recruited in the present study. The BMI change in the follow‐up was calculated as the annual percent change between BMI at last examination and that at baseline, and categorized into five groups: stable (−0.1 to <0.1 kg/m2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Smoking, body mass index (BMI), asbestos, and air pollution were regarded as traditional risk factors for lung cancer (3,4). The molecular genetics of lung cancer are also important, and the development of malignant lung tumors seems to be due to the multistage molecular pathogenesis, as well as the accumulation and combination of genetic factors and abnormalities (5).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, body mass index (BMI), asbestos, and air pollution were regarded as traditional risk factors for lung cancer (3,4). The molecular genetics of lung cancer are also important, and the development of malignant lung tumors seems to be due to the multistage molecular pathogenesis, as well as the accumulation and combination of genetic factors and abnormalities (5).…”
Section: Introductionmentioning
confidence: 99%
“…Associations of BMI with lung cancer have been reported across ethnic groups and across observational cohort studies; however, their findings are ambiguous. Based on relevant studies of the International Lung Cancer Consortium and the Chinese population, it was found that both an increase and a decrease in BMI could increase the risk of lung cancer and reduce the survival rate of lung cancer ( 48 , 49 ). Decreased BMI was also found to be associated with poorer overall survival of lung cancer, while weight gain increased the risk of death but was not statistically significant ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that a small residual number of confounding SNPs may still exist. To assess the association of each SNP with established common risk factors for lung cancer, including smoking, [ 42 ] alcohol consumption, [ 43 ] BMI, [ 44 ] hypertension, [ 45 ] diabetes, [ 46 ] and high cholesterol. [ 47 ] The Phenoscanner V2 website ( http://www.phenoscanner.medschl.cam.ac.uk/ ) was utilized.…”
Section: Methodsmentioning
confidence: 99%